West-African trypanosomiasis in a returned traveller from Ghana: an unusual cause of progressive neurological decline. (14th August 2014) - Elliott, Ivo; Patel, Trupti; Shah, Jagrit; Venkatesan, Pradhib
Abstract : West-African trypanosomiasis caused by Trypanosoma brucei gambiense is a rare imported infection presenting with somnolence, lymphadenopathy and wide-ranging neurological symptoms. A 67-year-old Caucasian man presented with a 10-month history of cognitive deterioration, ataxic gait, somnolence and urinary incontinence. His symptoms had progressed more rapidly over the course of a month prior to admission. Serological testing confirmed a diagnosis of West-African trypanosomiasis. The patient was successfully treated with eflornithine and made a good recovery. West-African trypanosomiasis should be considered in the differential diagnosis of unexplained cognitive decline in those with a relevant travel history. If left untreated, the condition is universally fatal.